2017
DOI: 10.3389/fmicb.2017.01751
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Herd Immunity to Amphibian Chytridiomycosis in Madagascar Based on the Defensive Function of Amphibian Skin Bacteria

Abstract: For decades, Amphibians have been globally threatened by the still expanding infectious disease, chytridiomycosis. Madagascar is an amphibian biodiversity hotspot where Batrachochytrium dendrobatidis ( Bd ) has only recently been detected. While no Bd -associated population declines have been reported, the risk of declines is high when invasive virulent lineages become involved. Cutaneous bacteria contribute to host innate immunity by providi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 59 publications
5
39
0
Order By: Relevance
“…In our data, the principal source of variance in inhibition was among bacterial strains, with the number of strains demonstrating broad‐spectrum facilitation of Bd GPL being approximately equal to the number exhibiting broad‐scale inhibition of the pathogen. These data support previous work suggesting B. dendrobatidis inhibition capability is distributed widely across bacterial genera (Antwis et al., ; Becker et al., ; Bletz, Myers, et al, ); several strains demonstrated at least weak inhibition for all 10 Bd GPLs but were spread across multiple genera with no clear pattern. That there is clear functional redundancy among genera in this host‐protective trait suggests it is not prudent to focus on any one genus in the search for beneficial probiotics (Becker et al., ), as highly divergent microbial communities can still possess similar functional traits (e.g., Bletz et al., ; Bletz, Perl, ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our data, the principal source of variance in inhibition was among bacterial strains, with the number of strains demonstrating broad‐spectrum facilitation of Bd GPL being approximately equal to the number exhibiting broad‐scale inhibition of the pathogen. These data support previous work suggesting B. dendrobatidis inhibition capability is distributed widely across bacterial genera (Antwis et al., ; Becker et al., ; Bletz, Myers, et al, ); several strains demonstrated at least weak inhibition for all 10 Bd GPLs but were spread across multiple genera with no clear pattern. That there is clear functional redundancy among genera in this host‐protective trait suggests it is not prudent to focus on any one genus in the search for beneficial probiotics (Becker et al., ), as highly divergent microbial communities can still possess similar functional traits (e.g., Bletz et al., ; Bletz, Perl, ).…”
Section: Discussionsupporting
confidence: 90%
“…Laboratory and field studies have shown host‐associated bacterial communities protect amphibians from B. dendrobatidis infection and that it is possible to artificially augment the microbiota with probiotic bacteria to improve survivorship in response to the pathogen (Becker et al., ; Bletz et al., ; Harris, Lauer, Simon, Banning, & Alford, ; Jani & Briggs, ; Kueneman et al., ; Muletz, Myers, Domangue, Herrick, & Harris, ; Walke et al., ). However, inhibitory capabilities of individual bacteria are not uniform across the variation presented by B. dendrobatidis (Antwis, Preziosi, Harrison, & Garner, ; Bletz, Myers, et al, ; Muletz‐Wolz et al., ). In addition, previous work has found either no (Becker et al., ) or weak evidence (Bletz, Myers, et al, ) of a phylogenetic signal in the ability of bacterial genera to inhibit a singular B. dendrobatidis isolate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, culturable species can account for a large fraction of the total relative abundance of a microbial community . Assays to determine the ability of a bacterial species to inhibit the pathogen have been conducted on agar plates and in 96‐well microtiter plates . Strains have ranged in effectiveness from highly inhibitory to facilitating pathogen growth in vitro .…”
Section: Next Steps In Probiotics Research and Application For Wildlimentioning
confidence: 99%
“…75 Assays to determine the ability of a bacterial species to inhibit the pathogen have been conducted on agar plates and in 96-well microtiter plates. 76 Strains have ranged in effectiveness from highly inhibitory to facilitating pathogen growth in vitro. Clearly, it is necessary to select an inhibitory strain, but it is less clear how inhibitory the strain must be in vitro in order to be effective (e.g., is 90% inhibition in vitro better than 80% inhibition once the strain is inoculated onto the host?).…”
Section: Probiotic Selectionmentioning
confidence: 99%